2022
DOI: 10.1093/braincomms/fcac269
|View full text |Cite
|
Sign up to set email alerts
|

Population-based assessment of nusinersen efficacy in children with spinal muscular atrophy: a 3-year follow-up study

Abstract: Nusinersen (Spinraza®) improves survival of infants with hereditary proximal spinal muscular atrophy and motor function in children up to 12 years. Population-based assessments of treatment efficacy are limited and confined to select cohorts of patients. We performed a nationwide, population-based, single-center cohort study in children with spinal muscular atrophy younger than 9.5 years at start of treatment in line with reimbursement criteria in the Netherlands. We assessed age-relevant motor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 60 publications
4
11
1
Order By: Relevance
“…In patients with type 2 SMA, steady improvements in the HFMSE score were observed at 1 and 2 years of follow-up, with a mean increase of 4.7 from baseline to the first year and 2.2 in the second year of treatment. These results were consistent with those observed in previous studies, reporting mean HFMSE score changes of 2.8-4.3 at year 1 from baseline and 0.8-1.5 from the first to the second year of follow-up (3,11,19). From the second to the third of year follow-up, a slow but steady increase in HFMSE score (mean 0.4) was observed in 12 patients who reached 3 years of follow-up.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In patients with type 2 SMA, steady improvements in the HFMSE score were observed at 1 and 2 years of follow-up, with a mean increase of 4.7 from baseline to the first year and 2.2 in the second year of treatment. These results were consistent with those observed in previous studies, reporting mean HFMSE score changes of 2.8-4.3 at year 1 from baseline and 0.8-1.5 from the first to the second year of follow-up (3,11,19). From the second to the third of year follow-up, a slow but steady increase in HFMSE score (mean 0.4) was observed in 12 patients who reached 3 years of follow-up.…”
Section: Discussionsupporting
confidence: 93%
“…This finding aligns with previous short-term follow-up studies, which reported a mean HINE-2 score increase of 2.2-3.2 from baseline to the first year and 0.9-1.9 from the first year to the second year (12,(16)(17)(18). The plateauing of motor function improvement between years 2 and 3 (mean 0.8 HINE-2 score improvement) in this study was consistent with findings from a recently published 3-year follow-up Dutch study, which reported a mean increase of 0.6 in HINE-2 scores between years 2 and 3 (11). In patients with type 2 SMA, steady improvements in the HFMSE score were observed at 1 and 2 years of follow-up, with a mean increase of 4.7 from baseline to the first year and 2.2 in the second year of treatment.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A recent meta-analysis on motor function in type II and III patients treated with nusinersen including all the real-world data available in the literature [45] shows that in all studies nusinersen treatment was associated with a favorable benefit in motor function that could be observed even when subdividing the results according to age and type of assessment. These results were different from those observed in natural history untreated cohorts who consistently showed negative changes [34,46]. New developments An ongoing phase 2/3 study, DEVOTE (NCT04089566), is currently exploring efficacy, safety, and PK of higher doses of nusinersen.…”
Section: Nusinersenmentioning
confidence: 71%
“…Subsequent real-life studies with type 1 SMA patients, including those using the drug in an expanded access program, further confirmed the positive effects of nusinersen on motor and respiratory function, as well as on the survival of patients with long-term illness and varying respiratory conditions. [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] The CHERISH trial was a placebo-randomized study that enrolled 126 patients with late-onset SMA aged 2 to 12 years. 41 The study demonstrated that patients who received nusinersen experienced clinically significant improvements in motor function compared to the control group.…”
Section: Regular Monitoring For Adverse Eventsmentioning
confidence: 99%